Instructional Components Involved in Content-Based Instruction (CBI) Tasks for Secondary School: Teachers’ and Students’ Thoughts - Maming, Khadijah; Yassi, Abdul Hakim; Nasmilah, Nasmilah; Amaluddin, Amaluddin (SALEE: Study of Applied Linguistics and English Education, 2024)
This study is directed to explore the teachers’ and students’ thoughts on instructional components involved in CBI tasks for productive skills learning in Indonesian secondary school context. There are ten teachers with more than five years of experience teaching English and eighty-six students taken as respondents. The findings reported the teacher voices focus on appropriate instructional components to support design of task-based learning through CBI approach, namely learning objective, learning material, learning activity, class organization, delivery mode, skill focus, use of media, learning resource, students’ worksheet and evaluation. In designing CBI tasks, learning objectives firstly formulated based on basic competence, the selection of learning material theme is surrounding-based materials and cultural-based materials, learning activities are organized in pairs and group in order to active interaction process in a learning atmosphere. They recommended to utilize web-based materials as learning resources and arrange students’ worksheet to empower the autonomous practical activity. Additionally, the students’ voices on contents of productive skills tasks clarified the tasks cover vocabulary, specific information, caption of picture, reading text, short dialogue and short paragraph as well as including the integration of language sub skills and skills. It is supportive contents for English learning tasks based on CBI approach.